Klischee und Realität: Fotografische Erfahrungsfragmente von Aufenthalten in Afrika - Heerbaart, Fabian; Kolossa, Kathrin; Limanski, Mareike; Rodekuhr, Peter André; Seifert, Marc; Stankowski, Sylvia; Thanassoula, Marilena (AAeO - Afrikanistik-Aegyptologie-Online, 2006)
How can one free oneself from the stereotypes that have been handed down through history and are constantly being perpetuated by the media today? Is a trip to Africa or specialist knowledge enough to distinguish between stereotype and reality?